Mapping global evidence on injuries/trauma due to sexual and gender-based violence for research prioritisation and development of guidelines to mitigate their impact: a scoping review protocol - Kuupiel, Desmond; Lateef, Monsurat A.; Pillay, Julian D.; Mchunu, Gugu G. (Systematic reviews, 2023)
Background The World Health Organization recognises injuries as a growing global public health problem. While there are several causes of injuries and trauma, relevant research is mostly centred on road traffic accidents, burns, and drowning with less focus on violence-related injuries/trauma such as sexual and gender-based violence (SGBV). To identify priority research topics, prioritisation, and development of practice guidelines to mitigate the impact of injuries/trauma resulting from SGBV, this systematic scoping review will aim to map and describe the range of research relating to injuries/trauma due to SGBV in the global context. Methods A scoping review guided by Arksey and O’Malley’s methodological framework will be conducted. Literature relating to injuries/trauma and SGBV will be searched in PubMed, SCOPUS, and PsycINFO, CINAHL, Web of Science, Google Scholar, Trip, guideline repositories, websites, and reference list of included articles. This study will include evidence sources focused on the epidemiological burden, guidelines for out-of-hospital and in-hospital care of victims, barriers or facilitators to reporting and obtaining healthcare, and approaches for mitigating injuries/trauma due to SGBV. The search will be limited to publications within 10 years (2012 to 2023). Two authors will apply the eligibility criteria to identify potentially relevant citations. The data will be extracted in duplicate and methodological quality assessed using varied tools (Mixed Method Quality Appraisal Tool; and Appraisal of Guidelines, Research and Evaluation instrument). The study will be reported in keeping with the Preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews. Discussion The scoping review will highlight existing literature on injuries/trauma due to SGBV and identify gaps to facilitate research prioritisation, development of guidelines, and resource allocation to alleviate the impact of injuries/trauma resulting from SGBV. This study’s findings will be disseminated via a series of meetings with key stakeholders (local and international) in the field of healthcare, policy, social welfare, GBV interest groups, and others. Also, the final scoping review results will be presented at relevant workshops, meetings, and conferences. Moreover, this study’s findings will be disseminated via journal publications and policy briefs.